A Comprehensive Review on the Chemical Properties, Plant Sources, Pharmacological Activities, Pharmacokinetic and Toxicological Characteristics of Tetrahydropalmatine - Du, Qinyun; Meng, Xianli; Wang, Shaohui (Frontiers in Pharmacology, 2022)
Tetrahydropalmatine (THP), a tetrahydroproberine isoquinoline alkaloid, is widely present in some botanical drugs, such as Stephania epigaea H.S. Lo [Menispermaceae; Radix stephaniae epigaeae], Corydalis yanhusuo (Y.H.Chou & Chun C.Hsu) W.T. Wang ex Z.Y. Su & C.Y. Wu [Papaveraceae; Corydalis rhizoma], and Phellodendron chinense C.K.Schneid [Berberidaceae; Phellodendri chinensis cortex]. THP has attracted considerable attention because of its diverse pharmacological activities. In this review, the chemical properties, plant sources, pharmacological activities, pharmacokinetic and toxicological characteristics of THP were systematically summarized for the first time. The results indicated that THP mainly existed in Papaveraceae and Menispermaceae families. Its pharmacological activities include anti-addiction, anti-inflammatory, analgesic, neuroprotective, and antitumor effects. Pharmacokinetic studies showed that THP was inadequately absorbed in the intestine and had rapid clearance and low bioavailability in vivo, as well as self-microemulsifying drug delivery systems, which could increase the absorption level and absorption rate of THP and improve its bioavailability. In addition, THP may have potential cardiac and neurological toxicity, but toxicity studies of THP are limited, especially its long-duration and acute toxicity tests. In summary, THP, as a natural alkaloid, has application prospects and potential development value, which is promising to be a novel drug for the treatment of pain, inflammation, and other related diseases. Further research on its potential target, molecular mechanism, toxicity, and oral utilization should need to be strengthened in the future.